Dietary intake of the bioactive pelargonidin may slow decline in multiple cognitive abilities: Prevention (non‐pharmacological): Developing ADRD non‐pharmacological intervention targets. (7th December 2020) - Holland, Thomas Monroe; Agarwal, Puja; Wang, Yamin; Desai, Pankaja; Dhana, Klodian; Barnes, Lisa L; Bennett, David A; Booth, Sarah; Morris, Martha Clare
Abstract: Background: Research has demonstrated a positive relationship between cognitive abilities and dietary intake of flavonoids, bioactives found in foods that have known antioxidant and anti‐inflammatory characteristics. We advance past research by investigating the association of dietary intake of an anthocyanidin subclass constituent, pelargonidin, found in berries especially, strawberries, on change in global cognition, episodic memory, semantic memory, working memory, perceptual speed, and visuospatial ability. Methods: This study was conducted in 961 Rush Memory and Aging Project (MAP), a prospective cohort study, consisting community‐dwelling participants in Chicago (aged 58 to 100 years), who were followed for an average of 6.3 (±2.7) years. MAP participants were asked to complete a validated semi‐quantitative food frequency questionnaire at baseline. Cognitive abilities were assessed annually using a battery of 19 standardized tests. Cognitive domain scores were regressed on baseline energy‐adjusted flavonoid pelargonidin, which was distributed into quartiles based on dietary intake in linear mixed models. Results: Our analytical sample of 961 participants had an average age of 81.4 (±7.2) years, and 15 (±3) years of education, 74% were female, 22% had at least one APOE‐ɛ4 allele, and 42% had a smoking history. Higher intake of pelargonidin, intake was inversely associated with decline in global cognition and multiple cognitive domains. In models adjusted for age, sex, education, APOE‐ɛ4, late life cognitive activity, smoking and physical activity, dietary intake of the highest quartile versus lowest quartile of pelargonidin was associated with slower decline in global cognition (β estimate=0.02, p=0.03; p‐trend=0.02), episodic memory (β=0.03, p=0.045; p‐trend=0.03), semantic memory (β=0.03, p=0.02; p‐trend=0.02), perceptual speed (β=0.02, p=0.02; p‐trend=0.01) and visuospatial ability (β=0.03, p=0.02; p‐trend=0.050). Non‐significant working memory was suggestive (β=0.02, p=0.07; p‐trend=0.07). Conclusion: Dietary intake of the anthocyanidin subclass constituent, pelargonidin, may slow decline of cognitive abilities in multiple domains with older age.